2006
DOI: 10.1158/1055-9965.epi-05-0753
|View full text |Cite
|
Sign up to set email alerts
|

Buccal DNA Collection: Comparison of Buccal Swabs with FTA Cards

Abstract: Collection and analysis of DNA, most commonly from blood or buccal cells, is becoming more common in epidemiologic studies. Buccal samples, which are painless to take and relatively easily collected, are often the preferred source. There are several buccal cell collection methods: swabs, brushes, mouthwash, and treated cards, such as FTA or IsoCode cards. Few studies have systematically compared methods of buccal cell collection with respect to DNA yield and amplification success under similar conditions. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 13 publications
1
38
3
Order By: Relevance
“…Mothers completed a questionnaire detailing folic acid supplement use with dose in the 3 months before and during pregnancy. Blood samples for DNA analysis were collected from case children and their parents at the treating hospital, while buccal cell samples were collected from control children and their parents at home using FTA cards (43). Case children also provided a buccal sample using this method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers completed a questionnaire detailing folic acid supplement use with dose in the 3 months before and during pregnancy. Blood samples for DNA analysis were collected from case children and their parents at the treating hospital, while buccal cell samples were collected from control children and their parents at home using FTA cards (43). Case children also provided a buccal sample using this method.…”
Section: Methodsmentioning
confidence: 99%
“…Case children also provided a buccal sample using this method. Punches taken from the cards were prepared for PCR as previously described (43), and samples were then subjected to whole genome amplification using the GenomiPhi V2 DNA Amplification Kit (GE Healthcare) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, increasing focus has been placed on buccal epithelial cells as an alternative DNA source [8][9][10][11][12][13][14][15], offering an easy-to-collect, non-invasive method [7,[10][11][12]16,17] with no reliance on medical staff [9,10,12]. Various methods have been described for the collection of buccal cells, including saliva [11,16,17], mouthwash [8,13,14,17], cytobrushes [13,14,17] and swabs [8][9][10][11]15]. Numerous studies have reported on the differences in DNA yield and quality between these collection methods.…”
Section: Introductionmentioning
confidence: 99%
“…In method 4 (bleach, tap water, ethanol), no detectable amplification was obtained with PCR of the precut control (Fig. 4, lane 1 Many studies used hole punches to excise material dried on filter paper [2][3][4]7,9,[12][13][14]16,18,20 ; however, only a few reports mention any protocols for detecting possible carryover or detection of false positives in filter-paperbased PCR methods. 9,11 Furthermore, many published studies overlooked any consideration for the possibility of such contamination.…”
mentioning
confidence: 99%
“…9,11 Furthermore, many published studies overlooked any consideration for the possibility of such contamination. 2,3,7,12,14,18 Quality assurance methods to avoid such contamination were reported by some investigators. 4,9,13,16,17,20 Some laboratories report punching holes in blank paper between samples to remove possible contaminants.…”
mentioning
confidence: 99%